The grindability of segmented grinding wheels produced by Vietnam in rough machining aluminum material - Nguyen, Thi Phuong Giang (НТУ "ХПИ", 2016)
Recently developed in Vietnam segmented grinding wheels is base on the fundamental of discontinuous machining is used to enhance the grindability of abrasive grains. The phenomenon of grinding chips adhesive to space between grains, that make the wheels became "dull", was reduce, special machining aluminum. In this paper, the evalution of segmented grinding wheel is based on the cutting performance. η is defined as a ratio between the discontinued regions and the of the grinding wheel’s working surface. There were five newly developed grinding wheels with (10.91%, 16.37%, 18.19%, 20.01% and 21.83% respectively) and one conventional η different η = 0%) were used to grind unhardened steel, hardened steel and aluminum. The results showed η grinding wheel (that segmented grinding wheels obtained a smoother surface in compared with conventional η = 20,01% for machining unhardened steel and at η = 18,19% machining aluminum material. On the other hand, segmented wheels with a less number of abrasive grains, show a higher efficiency for obtaining the smoother surface roughness than conventional wheels in the same working conditions. However, the mechanism of machining hardened and aluminum materials is a little bit different.

В статье рассматриваются сегментированные шлифовальные круги, разработанные недавно во Вьетнаме с опорой на основы прерывистой механической обработки, с целью повышения шлифующей способности зерен. Явление "засаливания" шлифовального круга, возникающее при налипании шлифованной стружки в межзеренном пространстве, при использовании таких кругов уменьшается, особенно при обработке алюминия. Исследовались круги с различным соотношением прерывистых участков и рабочей поверхности круга. Испытания кругов проводились для алюминиевого сплава, а также закаленной и незакаленной стали при различных режимах обработки, при этом выявлены некоторые отличия в механизме механической обработки.
Keywords: discontinuous machining; aluminum alloy; machining space; шлифование; прерывистая обработка; сегментированный шлифовальный круг